Supporting migrant entrepreneurship in entrepreneurial ecosystems: insights from Milan - Bolzani, Daniela; Mizzau, Lorenzo (Piccola Impresa / Small Business, 2020)
Human capital and social networks are two pillars of Entrepreneurial Ecosystems (EEs), which are nowadays increasingly shaped by international migration flows. Migrant entrepreneurs are at the same time locally present and culturally diverse from the mainstream host society, thus being prone to separation from the native community and participation to different social clusters, characterized by different venture types and access to institutions. Public agencies and incubators might be pivotal in facilitating the socialization of migrant entrepreneurs and the networked reciprocal exchange with other entrepreneurs. This paper sheds light on this overlooked issue by drawing on explorative interviews in Milan, Italy, in two incubators and the municipality. The findings show how the attraction and inclusion of migrant entrepreneurs is influenced both by EE attributes and by actors’ strategies and culture. This work offers novel insights contributing to the literature and policymaking on entrepreneurship and ecosystems